ANALISIS FILM SAYAP-SAYAP PATAH 2 : OLIVIA - Rahmawati, Ira; Tulus Rega Wahyuni E (JURNAL Dasarrupa: Desain dan Seni Rupa, 2024)
Film, as a medium of visual art, holds the power to reflect complex social and emotional realities. This study explores the representation of trauma and sacrifice in Sayap-Sayap Patah 2, a sequel that delves into the personal struggles of Indonesian police officers. The main focus of this research is how narrative and visual elements portray the psychological pressure, loss, and moral dilemmas faced by law enforcement personnel. Using a qualitative approach through narrative and visual analysis, I examine key scenes that highlight the human side of the characters. This study also investigates how such representation can foster audience empathy toward police officers, especially within the cultural and social context of Indonesia, where the police institution often carries public stigma. The findings are expected to provide new insights into the role of cinema in shaping public perception and contribute to the broader discourse in visual culture studies, media communication, and social psychology. This research also emphasizes the importance of film as a space for collective reflection and as a medium that bridges the gap between institutional narratives and individual experiences. Keywords: audience empathy, Indonesian film, law enforcement, sacrifice, trauma, visual representation.